Alpha Generation Slang by Content Creators on Tiktok - Raflis, Raflis; Novanta, Edrian (Jurnal Ilmiah Pendidikan Scholastic, 2025)
This research explores the use of slang by Alpha Generation on TikTok, focusing on content from creators @DamonSharpe, @KarenWazen, and @LearnWithPari, analyzed between December 1st-18th, 2024. Employing a descriptive qualitative approach, the research identifies and classifies 63 slang terms based on Allan and Burridge’s (2006) framework, categorizing them into five types: Fresh and Creative (52 terms, e.g., Sigma, Rizz), Clipping (4 terms, e.g., Sus, Fit), Flippant (4 terms, e.g., Fanum Tax), Acronym (2 terms, e.g., GOAT, FR), and Imitative (1 term, e.g., Finna). The study also examines their meanings and social functions, including addressing, initiating relaxed conversation, expressing impressions, and conveying emotions like anger or intimacy. Data were collected through observation, screenshots, and analysis of videos, with meanings derived from online sources and creator content. Findings highlight TikTok’s role as a dynamic platform for linguistic innovation, reflecting Alpha generation cultural and social identities. The predominance of Fresh and Creative slang underscores their creativity, while the varied functions illustrate slang’s role in fostering community and identity. This research offers insights into digital language evolution and suggests future studies explore slang across platforms and incorporate quantitative methods for broader sociolinguistic understanding.